2022
DOI: 10.3332/ecancer.2022.1380
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer in the MENA region, a bibliometric review

Abstract: Background Most Middle East and North Africa (MENA) countries record pancreatic cancer incidence rates that are above the world’s average. Reducing this burden requires evidence-based policies. This bibliometric review aims to examine the status of pancreatic cancer research in the MENA world, while systematically categorising publications across cancer care pathways. Methods We searched Scopus, Medline and PubMed for peer-reviewed publications related to both pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Armed conflicts and insurgencies have severely undermined the research capabilities of several MENA countries. Ranging from chronic underfinancing and poor infrastructure to deficient research culture ( 15 , 18 , 27 ), the challenges health researchers face in fragile and conflict-affected settings are numerous ( 11 , 28 ). Aiming to identify opportunities for improvement, our study aimed to map out published cancer research and highlight the characteristics of published research across 6 countries affected by conflict in the MENA region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Armed conflicts and insurgencies have severely undermined the research capabilities of several MENA countries. Ranging from chronic underfinancing and poor infrastructure to deficient research culture ( 15 , 18 , 27 ), the challenges health researchers face in fragile and conflict-affected settings are numerous ( 11 , 28 ). Aiming to identify opportunities for improvement, our study aimed to map out published cancer research and highlight the characteristics of published research across 6 countries affected by conflict in the MENA region.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the challenges mentioned above, the MENA region has been actively contributing to cancer research over the past two decades ( 15 18 ). However, and to the best of our knowledge, studies using bibliometric methods to analyze the knowledge output and trends of research on cancer in Fragile and Conflict-Affected Settings (FCS) in the MENA region are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research in this region has focused on the diagnosis and treatment approaches for pancreatic cancer, whereas there is a lack of high-quality public health and epidemiological research. 18 Therefore, future studies are needed to evaluate the epidemiology and risk factors associated with pancreatic cancer in MENA. 18 The present study also found that Saudi Arabia had the largest increase in the age-standardized incidence rate of pancreatic cancer in MENA.…”
Section: Discussionmentioning
confidence: 99%
“…18 Therefore, future studies are needed to evaluate the epidemiology and risk factors associated with pancreatic cancer in MENA. 18 The present study also found that Saudi Arabia had the largest increase in the age-standardized incidence rate of pancreatic cancer in MENA. In line with our findings, a previous study also found that the age-standardized incidence rate of pancreatic cancer increased from 1.7 to 2.2 and from 0.7 to 1.4 in Saudi male and female, respectively, between 2004 and 2015.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation